THE TVA AND ITS POWER—ACCOUNTING PROBLEMS. - Kohler, E. L. (The Accounting Review, 1948)
Abstract In the June, 1947, issue of the "Journal of Accountancy," appeared an article entitled "TVA's first audit by General Accounting Office (GAO) points way to businesslike evaluation." The article starts out with an editorial comment stating failure of TVA . . . to provide "yard-sticks" to measure private corporate operation; or, to be capable of being evaluated as going businesses, springs from lack of facts. General Accounting Office has made a commercial-type audit of Tennessee Valley Authority (TVA), plus recommendations, which show how TVA may be made comparable to commercial operation. . . failure to charge property taxes, depreciation, interest, and other expenses makes business men feel that government corporations, like TVA, cannot be considered commercial enterprises. The business man's objection grows out of the belief that government should not set up privileged competition with him, using his own money, and giving this competition the added advantages of freedom from taxes, interest, and other charges.